On Teaching Programming Fundamentals and Computational Thinking with Educational Robotics: A Didactic Experience with Pre-Service Teachers - João Piedade; Nuno Dorotea; Ana Pedro; João Filipe Matos (MDPI AG, 2020)
This study aims to analyze how pre-service informatics teachers design learning scenarios with robotics to teach programming fundamentals and to promote computational thinking skills. A descriptive and exploratory case study design was implemented with 26 pre-service informatics teachers. Data were collected from the participants using qualitative and quantitative instruments. The main results pointed out the affordances and possibilities of the use of learning scenarios with robotics to teach programming fundamentals and to promote computational thinking skills as well as a strong path to promote the application of contents of the other Science, Technology, Engineering, Arts and Mathematics (STEAM) areas. Another significant finding was the impact of the didactic experience on the level of interest and self-confidence of the pre-service teachers in using robotics for teaching purposes. The results showed the importance of these didactics experiences to the pre-service teachers preparation and to apply the pedagogic approaches they have learned in theory in practical activities and to transfer this knowledge to new pedagogical situations and problems.